Author Correction: Glomerulocapillary miRNA response to HLA-class I antibody in vitro and in vivo - Falko M. Heinemann (Nature Portfolio, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.